Feeding Food Wastes to Livestock - Robert O. Myer; Holly Johnson (EDIS)
Revised! AN-082, a 2-page fact sheet by Robert Myer and Holly Johnson, discusses the use of wasted food from the food service industry and grocery stores as animal feed, Florida and federal regulations governing its use for swine and cattle. Includes references. Published by the UF Department of Animal Sciences, April 2007.